Gender differences in the use of emotive language in TED Talks - Mohd Taib, Najiha; C Suppiah, Puspalata (Universiti Teknologi MARA, 2024)
The emergence of the Internet brought about new modes of communication and personal expression. The precise se-lection of words or phrases holds significant importance, as they have the capacity to evoke a wide range of reactions, aligning the audience’s feelings with the purpose of the message. This study sought to explore how male and female political figures utilise emotive language in TED Talks, examining differences in their usage and quantity of emotive language. Through a homogenous purposive sampling method, similar samples were selected and transcribed via the YouTube Transcript tool. Reference was also made to Jakobson’s (1960) framework to analyse two TED Talks, My Trials and Tribulations and From Enemy to Valentines. The novelty of this study lies in its exploration of the emo-tional dimension within internet media discourse. Notably, it reveals that the female speaker outpaced the male speak-er in articulating negative emotions to craft a compelling presentation. In essence, the study demonstrates that both genders conveyed comparable emotions stemming from traumatic experiences. This research provides valuable in-sights for speakers, the public, and future researchers by illustrating how gender variations in emotional expression in-fluence the use of emotive language and communication approaches across genders.